Retrospective database analysis of clinical outcomes and costs for treatment of abnormal uterine bleeding among women enrolled in US Medicaid programs - Bonafede MM; Miller JD; Laughlin-Tommaso SK; Lukes AS; Meyer NM; Lenhart GM (Dove Medical Press, 2014)
Machaon M Bonafede,1 Jeffrey D Miller,1 Shannon K Laughlin-Tommaso,2 Andrea S Lukes,3 Nicole M Meyer,1 Gregory M Lenhart1 1Truven Health Analytics, Cambridge MA, 2Mayo Clinic, Department of Obstetrics and Gynecology, Rochester, MN, 3Women's Wellness Clinic and Research Center, Durham, NC, USA Background: Women with abnormal uterine bleeding (AUB) may be treated surgically with hysterectomy or global endometrial ablation (GEA), an outpatient procedure. We compared the costs and clinical outcomes of these surgical procedures for AUB among women in Medicaid programs.Methods: The Truven Health MarketScan® Medicaid Multi-State Database was used to identify Medicaid women aged 30–55 years with AUB who newly initiated GEA or hysterectomy (index event) during 2006–2010. Patients were required to have 12 months of continuous enrollment pre-index and post-index. Baseline characteristics were assessed in the pre-index period; health care utilization and costs (2011 USD), treatment complications, and reinterventions were assessed in the post-index period.Results: Of 1,880 women who met the study criteria (mean age 40.7 years), 53.4% were Caucasian, 33.1% were African-American, and 2.3% were Hispanic; many (42.8%) received their Medicaid eligibility due to disability. Similar proportions received GEA (50.9%) or hysterectomy (49.1%). At baseline, both groups also had similar Deyo-Charlson Comorbidity scores (0.65), and use of antibiotics (69.4%), nonsteroidal anti-inflammatory drugs (56.3%), and oral contraceptives (5.3%). More hysterectomy patients than GEA patients had a treatment-related complication (52% versus 36%, respectively, P<0.001). Initial treatment costs were higher for hysterectomy ($11,270) than for GEA ($3,958, P<0.001); monthly gynecology-related costs in the remainder of the year were not significantly different for hysterectomy ($63) and GEA ($16, P=0.11).Conclusion: Hysterectomy was nearly three times more costly than GEA for initial treatment of AUB, and associated with more treatment-related complications. These results may be informative in the context of new federal mandates for Medicaid expansion, which are likely to focus on cost savings through use of outpatient treatments such as GEA. Keywords: abnormal uterine bleeding, menorrhagia, endometrial ablation, hysterectomy, Medicaid